Irregular-Shaped Hematoma Predicts Postoperative Rehemorrhage After Stereotactic Minimally Invasive Surgery for Intracerebral Hemorrhage - Wang, Likun; Luo, Sheng; Ren, Siying; Yu, Hui; Shen, Guiquan; Wu, Guofeng; Yang, Qingwu (Frontiers in Neurology, 2022)
Background and Purpose Minimally invasive surgery (MIS) is performed to treat patients with intracerebral hemorrhage (ICH) with favorable results. However, postoperative rehemorrhage is a significant risk. The present study retrospectively analyzed the association of irregular-shaped hematoma with postoperative rehemorrhage following stereotactic MIS (sMIS). Methods We enrolled 548 patients with spontaneous ICH who underwent sMIS. Based on the hematoma shape, the patients were assigned to the regular-shaped hematoma group (RSH group; 300 patients) or irregular-shaped hematoma group (ISH group; 248 patients). Logistic regression analysis was performed to identify the predictors of postoperative rehemorrhage after sMIS for ICH evacuation. The functional outcome was assessed using the modified ranking scale (mRS) score at discharge. A receiver operating characteristic (ROC) curve was used to confirm the results. Results Among 548 patients with ICH who underwent sMIS, 116 developed postoperative rehemorrhage. Postoperative rehemorrhage occurred in 30.65% of patients with ISH and 13.30% with RSH (P < 0.01), with a significant difference between the ISH and RSH groups. Among 116 patients with postoperative rehemorrhage, 76 (65.52%) showed ISH on CT scan. In 432 patients without postoperative rehemorrhage, only 39.81% displayed ISH. The logistic regression analysis demonstrated that ISH could independently predict postoperative rehemorrhage. The sensitivity, specificity, positive predictive value, and negative predicative value were 0.655, 0.398, 0.655, and 0.602, respectively. The ROC analysis confirmed the value of ISH in predicting postoperative rehemorrhage with an area under the curve of 0.629. Conclusions Irregular-shaped hematoma was an independent predictor of postoperative rehemorrhage after sMIS.